High Prevalence of Weight Gain in Childhood Brain Tumor Survivors and Its Association With Hypothalamic-Pituitary Dysfunction. Issue 11 (10th April 2021) - van Schaik, Jiska; van Roessel, Ichelle M. A. A.; Schouten-van Meeteren, Netteke A. Y. N.; van Iersel, Laura; Clement, Sarah C.; Boot, Annemieke M.; Claahsen-van der Grinten, Hedi L.; Fiocco, Marta; Janssens, Geert O.; van Vuurden, Dannis G.; Michiels, Erna M.; Han, Sen K. S.; et al.
Abstract : PURPOSE: Childhood brain tumor survivors (CBTS) are at risk for developing obesity, which negatively influences cardiometabolic health. The prevalence of obesity in CBTS may have been overestimated in previous cohorts because of inclusion of children with craniopharyngioma. On the contrary, the degree of weight gain may have been underestimated because of exclusion of CBTS who experienced weight gain, but were neither overweight nor obese. Weight gain may be an indicator of underlying hypothalamic-pituitary (HP) dysfunction. We aimed to study prevalence of and risk factors for significant weight gain, overweight, or obesity, and its association with HP dysfunction in a national cohort of noncraniopharyngioma and nonpituitary CBTS. METHODS: Prevalence of and risk factors for significant weight gain (body mass index [BMI] change ≥ +2.0 standard deviation score [SDS]), overweight, or obesity at follow-up, and its association with HP dysfunction were studied in a nationwide cohort of CBTS, diagnosed in a 10-year period (2002-2012), excluding all craniopharyngioma and pituitary tumors. RESULTS: Of 661 CBTS, with a median age at follow-up of 7.3 years, 33.1% had significant weight gain, overweight, or obesity. Of the CBTS between 4 and 20 years of age, 28.7% were overweight or obese, compared with 13.2% of the general population between 4 and 20 years of age. BMI SDS at diagnosis, diagnosis of low-grade glioma, diabetes insipidus, and central precocious puberty were associated with weight gain, overweight, or obesity. The prevalence of HP dysfunction was higher in overweight and obese CTBS compared with normal-weight CBTS. CONCLUSION: Overweight, obesity, and significant weight gain are prevalent in CBTS. An increase in BMI during follow-up may be a reflection of HP dysfunction, necessitating more intense endocrine surveillance.